The Value of Advice through On People's Story - Dian Marisha; Yusni Khairul Amri (Lakhomi Journal Scientific Journal of Culture, 2023)
Advice values in folklore stories can educate in taking lessons and role models that are worthy of being guided by and then used as examples of bad behavior and those that are not good not to emulate. The value of valuable advice, namely: being sincere and selfless and forgiving their children, Forgiving others is a commendable deed, The child's respect for both parents is manifested in sentences that show obedience to both parents. Folklore often reflects the creativity of traditional societies while still holding fast to tradition as a manifestation of creativity that is alive and passed down from generation to generation. Thus, folklore stories remain oriented towards local ethnic values. Value (value) has always been a measure in determining truth and justice that comes from religious content, logic, and the norms prevailing in society. Interpreting values in Folklore by interpreting a behavioral trend that originates from psychological symptoms such as: desires, motives, attitudes, needs, and beliefs that are owned, so that the values of Folklore can be used as parametric educational values, religiosity, social values, and norms as ethnic bias.